Putting virtues in context: engaging the VIA classification of character strengths in caregiving for orphans and vulnerable children across cultures. Issue 6 (2nd November 2019) - Kinghorn, Warren A.; Keyes, Corey L. M.; Parnell, Heather E.; Eagle, David E.; Biru, Blen M.; Amanya, Cyrilla; Vann, Vanroth; Krishna Kaza, Venkata Gopala; Tzudir, Senti; Saddo, Yohannes Benyam; Whetten, Kathryn; Proeschold-Bell, Rae Jean
ABSTRACT: The VIA Classification of Character Strengths has broken important ground for measuring character strengths across cultures. Because the VIA Classification is a closed system of abstract strengths, however, it is unknown how end-users engage strengths in particular cultural and practical contexts, define strengths for themselves, or identify additional strengths. In this study, residential care directors (n = 18) and other caregivers (n = 64) for orphans and vulnerable children (OVCs) in five distinct global locations prioritized with a card-sort the VIA Character Strengths most important for the work of caregiving, defined these strengths, and proposed additional strengths. Supervisors were then asked how caregivers embodied their prioritized strengths. Participants most frequently prioritized Love, Honesty, Forgiveness, and Kindness as important for caregiving; demonstrated high concordance but also some deviation from the definitions of the VIA Classification; and proposed additional strengths (e.g. Caring, Self-drive, and Initiative) that were perceived not to overlap with existing VIA Character Strengths.